ANAK BERKEBUTUHAN KHUSUS DAN PERMASALAHANNYA (STUDI DI KEMUKIMAN PAGAR AIR KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR) - Maisarah, Siti; Saleh, Julianto; Husna, Nurul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
In this study, it examines children with special needs and their problems. The problem experienced by one crew member was that parents did not provide education to ABK, parents abandoned ABK and also parents did not provide good service to ABK. Although parents receive ABK in the family, parents do not provide education for various reasons. One family does not provide education on the grounds that the school specifically ABK does not want to accept children with ABK with Palsy. The schools that want to accept children with special needs are far from their homes. This study aims to determine the problems experienced by ABK in the Water Fence Settlements of Ingin Jaya District, Aceh Besar District. This study uses a descriptive method with a qualitative approach. The results of this study the problems experienced by ABK are not properly educated, not taken care of as other children and neglected. But on the other hand, ABK has the potential and expertise even the potential it has exceeds other normal children. Parents in Islam are required or make sure their children are normal or not normal to not be weak children. In every Pagar Air Settlement Village, there are different crew members.Keywords: Children with Special Needs, Problems